PELAKSANAAN GERAKAN LITERASI SEKOLAH DI SDN 1 SRIKATON KECAMATAN ANAK TUHA - Anindita, Elisa; Agus Wibowo; Hadi Pranoto (Universitas Muhammadiyah Metro, 2024)
The purpose of this study is to find out how the planning of the school literacy movement is, how the implementation of the school literacy movement is, how to evaluate the school literacy movement and what are the supporting and inhibiting factors for the implementation of the literacy movement. This type of research is descriptive with a qualitative approach. The subjects in this study were one class teacher, the principal, and one student. The researcher acted as observer and data collector. Data were obtained by using direct interview method with research subjects. The results of this study conclude that the first is planning the literacy movement planning literacy needs through interviews and observations made by teachers to students.